WOMEN AND NATURE: ECOPSYCOCHOLOGICAL FILM READING - Derdous, Rym (PEOPLE: International Journal of Social Sciences, 2024)
Nature-based studies yielded significant results concerning the psychological benefits of nature exposure. As such, ecopsychology is concerned with the relation human beings have with the surrounding environment. Using a multimodal approach comprising textual film analysis and ecopsychology, this work examines natural elements in the films Papicha (2019) and Clair Obscur (2016) and the psychological effects ensuing a nature experience. Papicha (2019) directed by Mounia Meddour tells the story of Nejdma who struggles to achieve her dream as a fashion designer in a demanding society. Likewise, Chenaz and Elmas in Clair Obscur (2016) defy society in their way to regain their independent autonomous selves. Although from two different cinematic traditions, the former Algerian and the latter Turkish, the films provide an audio-visual experience that traces the main characters’ state of mind before and post nature exposure and their journeys towards self-discovery and empowerment. The emphasis on solely female protagonists, in addition to nature, promotes feminist ecopsychological thinking. It provides an opportunity to explore feminist perspectives by highlighting the connection between women and nature portrayed through these female protagonists' experiences.